Precision Medicine: Omics-tailored Clinics - Acuner-Ozbabacan, Saliha Ece (International Journal of Innovative Research in Medical Science, 2019)
We are now in a data-driven biomedical era in which the aim of precision medicine is to collect, investigate and interpret the omics data effectively and integratively to be able to implement the results in healthcare with high accuracy. Recent promising applications show that molecularly classifying a disease into subpopulations is beneficial for both patients and drug developers.